Can we simplify or improve long-term risk stratification for patients with ST-segment elevation myocardial infarction undergoing primary intervention?. (14th October 2021) - Dias Ferreira Reis, J P; Rio, P; Timoteo, A; Ramos, R; Ferreira, M L; Cruz Ferreira, R
Abstract: Background: Various scores have been developed to predict early to mid-term prognosis after ST-elevation myocardial infarction (STEMI). The aim of this study was to compare the predictive value of 7 popular risks scores for the long-term outcome of STEMI patients undergoing primary intervention, and to find an easy model with similar or superior predictive and discriminative ability. Methods: Patients who underwent primary PCI from January 2003 through August 2007 in a single tertiary-center were analysed (n=665) using a dedicated prospective registry. Global Registry for Acute Coronary Events (GRACE), GRACE 6 months, Thrombolysis In Myocardial Infarction (TIMI) STEMI, dynamic TIMI, TIMI risk index, Primary Angioplasty in Myocardial Infarction (PAMI) and Zwolle primary percutaneous coronary intervention (PCI) index were calculated for each patient. We assessed, through the C statistic in receiver-operating characteristic analysis, the predictive accuracy of these scores using all-cause mortality at 5 year as an endpoint. With multivariate regression analysis the variables with highest predictive ability were applied to build a model. Results: All-cause mortality at 5 years after primary PCI was 22.1%. The risk scores showed moderate predictive ability, GRACE (0.759, 95% confidence interval (CI) 0.712–0.805), GRACE 6 months (0.802, 95% CI 0.759–0.845), TIMI STEMI (0.744, 95% CI 0.696–0.791), dynamic TIMI (0.774, 95% CI 0.727–0.820), TIMI risk index (0.757, 95% CI 0.710–0.803), PAMI (0.753, 95% CI 0.707–0.800) and Zwolle index (0.749, 95% CI 0.703–0.795). Six independent predictors of 5-year mortality were identified (age >70 years, history of MI, history of stroke, heart tare above 85 beats per min, 3-vessel disease and in-hospital adverse events) and the model built had similar discriminative performance in estimation of probabilities of death (0.804, 95% CI 0.762–0.846, p=0.953 for difference with GRACE score). Conclusions: The prediction values of currently recommended risk scores are moderate for long-term perspective (5-year). The simplified risk stratification score for STEMI and primary angioplasty using only six variables demonstrates accuracy similar to the more advanced risk scores. FUNDunding Acknowledgement: Type of funding sources: None.